2018
DOI: 10.1371/journal.ppat.1006870
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma mansoni SmKI-1 serine protease inhibitor binds to elastase and impairs neutrophil function and inflammation

Abstract: Protease inhibitors have important function during homeostasis, inflammation and tissue injury. In this study, we described the role of Schistosoma mansoni SmKI-1 serine protease inhibitor in parasite development and as a molecule capable of regulating different models of inflammatory diseases. First, we determine that recombinant (r) SmKI-1 and its Kunitz domain but not the C-terminal region possess inhibitory activity against trypsin and neutrophil elastase (NE). To better understand the molecular basis of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
62
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 68 publications
(72 reference statements)
2
62
0
1
Order By: Relevance
“…The worms secrete serine protease inhibitors (serpins) which counteract the potentially lethal effects of these host intestinal proteases and thereby likely play a key protective role in preventing proteolytic enzyme attack, ensuring survival of E. granulosus within its canine hosts. These, along with molecular chaperones, neurotransmitter receptors and transporters, and other protease inhibitors, specifically expressed in adult worms, likely represent additional vaccine candidates that warrant future study (261,285,(321)(322)(323).…”
Section: Improving Vaccine Developmentmentioning
confidence: 99%
“…The worms secrete serine protease inhibitors (serpins) which counteract the potentially lethal effects of these host intestinal proteases and thereby likely play a key protective role in preventing proteolytic enzyme attack, ensuring survival of E. granulosus within its canine hosts. These, along with molecular chaperones, neurotransmitter receptors and transporters, and other protease inhibitors, specifically expressed in adult worms, likely represent additional vaccine candidates that warrant future study (261,285,(321)(322)(323).…”
Section: Improving Vaccine Developmentmentioning
confidence: 99%
“…SPIs are widely distributed in a variety of species [29,30]. They are able to inhibit the catalytic activity of proteolytic enzymes and guarantee the inhibiting proteolysis of proteinase, which are important in poisonous animals' biological processes for survival [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Lyophilized human plasma (400100, Cayman, Ann Arbor, MI, USA) was resuspended in sterile water according to the instruction, then ShSPI was added to each equivalent volume with a final concentration of 500 nM, and samples were co-incubated at 37 • C for two days. Triplicate samples were collected at selected time points (0, 6,12,18,24,30,36,42, and 48 h) and protease activity was tested as described above.…”
Section: Plasma Stabilitymentioning
confidence: 99%
“…In chronic diseases, eggs trapped in various tissues induce the formation of granulomatous inflammation, which subsequently results in fibrosis that causes many of the pathological conditions. It is believed that parasites definitely cause damage to their host, and the host resists against the invading parasites by its immune response (Han et al, 2009;The Schistosoma japonicum Genome Sequencing and Functional Analysis Consortium, 2009;deWalick et al, 2012;Duan et al, 2014;Morais et al, 2018;Roderfeld et al, 2018). However, several studies have already observed that host factors such as the immune factors can modulate parasite development and maturation (Amiri et al, 1992;Hernandez et al, 2004;LoVerde et al, 2009;Beckmann et al, 2010;deWalick et al, 2012).…”
mentioning
confidence: 99%